The Lease Sale Contract is Protection for the Beneficiary or the Developer of the Real Estate Upgrade? - Bouabdellah, Naoual; Ladguach, Rahima (Journal of Legal Studies and Researches, 2022)
The Algerian legislator was strict in the direction of the beneficiary in the contract of sale on rent, given the obligations imposed on the latter and made its executors liable to penalty. In this research paper, we examine the obligations of the beneficiary of housing in the framework of the lease sale contract, by addressing the position of the Algerian legislator in regulating the provisions of this contract, in order to highlight its purpose of emphasizing the beneficiary at a time when he shouls have sought protection for him, as he has done in order forms of real estate promotion.